Cardinality-constrained structured data-fitting problems - Fan, Zhenan; Fang, Huang; Friedlander, Michael P. (Open Journal of Mathematical Optimization)
A memory-efficient solution framework is proposed for the cardinality-constrained structured data-fitting problem. Dual-based atom-identification rules reveal the structure of the optimal primal solution from near-optimal dual solutions, which allows for a simple and computationally efficient algorithm that translates any feasible dual solution into a primal solution satisfying the cardinality constraint. Rigorous guarantees bound the quality of a near-optimal primal solution given any dual-based method that generates dual iterates converging to an optimal dual solution. Numerical experiments on real-world datasets support the analysis and demonstrate the efficiency of the proposed approach.